Glucose Absorption by the Bacillary Band of Trichuris muris. - Tina V A Hansen; Michael Hansen; Peter Nejsum; Helena Mejer; Matthew Denwood; Stig M Thamsborg (Public Library of Science (PLoS), 2016)
BACKGROUND:A common characteristic of Trichuris spp. infections in humans and animals is the variable but low efficacy of single-dose benzimidazoles currently used in mass drug administration programmes against human trichuriasis. The bacillary band, a specialised morphological structure of Trichuris spp., as well as the unique partly intracellular habitat of adult Trichuris spp. may affect drug absorption and perhaps contribute to the low drug accumulation in the worm. However, the exact function of the bacillary band is still unknown. METHODOLOGY:We studied the dependency of adult Trichuris muris on glucose and/or amino acids for survival in vitro and the absorptive function of the bacillary band. The viability of the worms was evaluated using a motility scale from 0 to 3, and the colorimetric assay Alamar Blue was utilised to measure the metabolic activity. The absorptive function of the bacillary band in living worms was explored using a fluorescent glucose analogue (6-NBDG) and confocal microscopy. To study the absorptive function of the bacillary band in relation to 6-NBDG, the oral uptake was minimised or excluded by sealing the oral cavity with glue and agarose. PRINCIPAL FINDINGS:Glucose had a positive effect on both the motility (p < 0.001) and metabolic activity (p < 0.001) of T. muris in vitro, whereas this was not the case for amino acids. The 6-NBDG was observed in the pores of the bacillary band and within the stichocytes of the living worms, independent of oral sealing. CONCLUSIONS/SIGNIFICANCE:Trichuris muris is dependent on glucose for viability in vitro, and the bacillary band has an absorptive function in relation to 6-NBDG, which accumulates within the stichocytes. The absorptive function of the bacillary band calls for an exploration of its possible role in the uptake of anthelmintics, and as a potential anthelmintic target relevant for future drug development.